2018
DOI: 10.1007/s40299-018-0376-3
|View full text |Cite
|
Sign up to set email alerts
|

Study-Abroad Experiences of Two South Korean Undergraduate Students in an English-Speaking and a Non-English-Speaking Country

Abstract: Benefits of the study-abroad (SA) experience have been reported in many studies. However, most prior studies on EFL students' SA experiences track students in relatively short ESL programs during school vacation months. In addition, EFL learners' SA experiences in nonEnglish-speaking countries, where English is not the L1, remain underexplored. Applying case study methodology and gathering data from monthly reports during SA, and pre-and post-SA interviews, this study aimed to investigate SA experiences of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The impact of English proficiency gains is also certainly determined by study abroad country choice (Nam, 2018) because the offered programs by host institutions of participants,…”
Section: The Country Where Participants Are Staying (Studying Abroad)mentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of English proficiency gains is also certainly determined by study abroad country choice (Nam, 2018) because the offered programs by host institutions of participants,…”
Section: The Country Where Participants Are Staying (Studying Abroad)mentioning
confidence: 99%
“…These experiences could happen not only to migrant workers, but also to students (Block, 2009). Nam (2018) found that the English-speaking countries where the students live abroad have power in relation to ELT Echo : The Journal of English Language Teaching in Foreign Language Context (2021), Vol 6(1) Published by English Language Teaching Department, IAIN Syekh Nurjati Cirebon, Indonesia. p-ISSN: 2579-8170, e-ISSN: 2549-5089 ELT Echo : The Journal of English Language Teaching in Foreign Language Context journal homepage: https://syekhnurjati.ac.id/jurnal/index.php/eltecho construct participants" second language proficiency, which extended to identity.…”
Section: Introductionmentioning
confidence: 99%
“…Kang's (2004) investigation, although was set in a study abroad context as well, focused on Korean learners in the United States. Also, another recent effort to investigate Korean learners in study abroad contexts was set in non-Asian context (Nam, 2018). Methodologically, Edwards (2006) suggested continued research involving qualitative methods.…”
Section: Wtc Among Korean Participantsmentioning
confidence: 99%
“…In the past, students' mobility focused on English-speaking countries. However, in recent years, the number of students from Asia and the Pacific region has also increased, and 53% of all students enrolled in higher education in 2011 were from China, India, and Korea (Organization for Economic Cooperation and Development [OECD], 2012;Nam, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the past, students' mobility focused on English-speaking countries. However, in recent years, the number of students from Asia and the Pacific region has also increased, and 53% of all students enrolled in higher education in 2011 were from China, India, and Korea (Organization for Economic Cooperation and Development [OECD], 2012;Nam, 2018).The speed of population decline and aging in developed and developing countries is another relevant issue affecting higher education worldwide. Japan has a rapidly aging population and low birth rate, resulting in a decrease of the youth and working age populations.…”
mentioning
confidence: 99%